GATA3 Truncation Mutants Alter EMT Related Gene Expression via Partial Motif Recognition in Luminal Breast Cancer Cells - Saotome, Mika; Poduval, Deepak Balakrishnan; Nair, Renju; Cooper, Mikhala; Takaku, Motoki (Frontiers in Genetics, 2022)
GATA3 is known to be one of the most frequently mutated genes in breast cancer. More than 10% of breast tumors carry mutations in this gene. However, the functional consequence of GATA3 mutations is still largely unknown. Clinical data suggest that different types of GATA3 mutations may have distinct roles in breast cancer characterization. In this study, we have established three luminal breast cancer cell lines that stably express different truncation mutants (X308 splice site deletion, C321 frameshift, and A333 frameshift mutants) found in breast cancer patients. Transcriptome analysis identified common and distinct gene expression patterns in these GATA3 mutant cell lines. In particular, the impacts on epithelial-to-mesenchymal transition (EMT) related genes are similar across these mutant cell lines. Chromatin localization of the mutants is highly overlapped and exhibits non-canonical motif enrichment. Interestingly, the A333 frameshift mutant expressed cells displayed the most significant impact on the GATA3 binding compared to X308 splice site deletion and C321fs mutants expressed cells. Our results suggest the common and different roles of GATA3 truncation mutations during luminal breast cancer development.